Análisis de escleroma para la clasificación de nueva especie de Pacifigorgia (2020)
The Octocorales are a phylogenetic group of soft corals, little information is currently available about them. Therefore, it is common to find individuals that do not fit into any of the known species. Additionally, traditional methods for the categorization of individuals have limitations that hinder their identification. Therefore, it is necessary to promote the use of new tools that ease and complement this process. In this study, a comparison was made of the composition of the skeleton made of calcium carbonate, that presents individuals of the genus Pacifigorgia, which could not be identified with traditional methods, with the composition present in individuals of the species Pacifigorgia eximia. After reviewing the sclerome of both individuals, as well as a genetic and morphological review of both, it was possible to determine that the population in question fails to meet the necessary characteristics to enter the P. eximia species.